2008
DOI: 10.1097/01.pcc.0000298643.48547.83
|View full text |Cite
|
Sign up to set email alerts
|

Candida colonization and candidemia in a pediatric intensive care unit

Abstract: Monitoring for colonization with Candida species in children undergoing treatment for severe sepsis or sepsis shock in PICU for >5 days may offer opportunity for early intervention for prevention of candidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
59
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 31 publications
(29 reference statements)
13
59
0
10
Order By: Relevance
“…This has been also reported in other studies which have pointed to the significant role of Candida colonization as an important risk factor for candidemia even in a non-neonatal population [12]. Moreover, several studies have shown that ICU patients with mucosal Candida colonization, particularly if multifocal, are at higher risk for invasive candidiasis, and that colonization selects a population amenable to antifungal prophylaxis or empirical therapy [31].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This has been also reported in other studies which have pointed to the significant role of Candida colonization as an important risk factor for candidemia even in a non-neonatal population [12]. Moreover, several studies have shown that ICU patients with mucosal Candida colonization, particularly if multifocal, are at higher risk for invasive candidiasis, and that colonization selects a population amenable to antifungal prophylaxis or empirical therapy [31].…”
Section: Discussionmentioning
confidence: 50%
“…However, few data have been reported regarding the colonizationinfection shift outside the NICU where colonization by Candida species was found to be an independent predictor of candidemia in children undergoing treatment for severe sepsis or sepsis shock in PICU [12].…”
Section: Introductionmentioning
confidence: 99%
“…(14-17) Twenty-fi ve of forty-eight (52.1%) colonized patients carried C.albicans and 15/48 (31.25%) C.parapsilosis. Th e rate of C.parapsilosis colonization is modestly higher than data reported in other paediatric units (2,18,19), so it could be considered an important and distinctive feature of our NICU, requiring deeper analysis. We identifi ed as risk factors for Candida spp.…”
Section: Discussionmentioning
confidence: 39%
“…A study in India showed similar trends, adding the observation that central venous catheters were a risk factor for colonization. In the same study, C. tropicalis was the most common organism in blood cultures (Singhi et al, 2008). In our study, the median postnatal age at onset of infection was 21.75 days (range: 14-28 days); moreover, two cases were successfully treated using antibiotics within one week.…”
Section: Discussionmentioning
confidence: 72%